OWC형 파력발전 공기챔버의 공기감쇠력 실험 연구 - 최학선(HARK-SUN CHOI); 홍석원(SEOK-WON HONG); 김진하(JIN-HA KIM); 류재문(JAE-MOON LEW) (Han-guk haeyang gonghak hoeji (Online), 2004)
Pneumatic damping through an orifice-type duct for an OWC-type wave energy device is studied experimentally. Forced oscillation tests are used to measure chamber pressure and velocity of air-flow through an orifice. Pneumatic damping coefficients are deducted from the experimental research, and the influence of frequency, heave amplitude, and orifice size are discussed. Finally, two formulas are proposed for the estimation of non-dimensional pneumatic damping coefficient by regression analysis. The proposed formula proves to be a reliable method for practical application.